Peran Atlet Basket Indonesian Basketball League (IBL) Sebagai Ayah dalam Perkembangan Sosial-Emosional Anak Usia Dini - Lydia Anggraeni Denthi Permatasari; Heru Kurniawan; Akhmad Multazim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The socio emotional aspect is crucial for early childhood development because it forms the basis for children's ability to understand themselves, recognize their feelings, relate to others, and adapt to their environment. Children learn to recognize and understand the social world through their relationships with their parents. Therefore, the purpose of this study was to determine the role of fathers who are professional athletes in the socio-emotional development of early childhood. The method used was descriptive research. Data were collected through watching videos, viewing photos, and taking notes. Data were analyzed using content analysis within the framework of attachment theory. The results of the study were activities that demonstrate the role of fathers as role models, playmates, and caregivers.